Dampak Label Syariah pada Keputusan Investasi Investor Pemula dengan Agama sebagai Moderasi - Lestari, Siti Sinta (Keizai, 2024)
Investing in shares in Islam must pay attention to clear sources and elements, including 3 things that must be considered, namely, before buying shares, carry out fundamental analysis or technical analysis, these two methods of analysis will prevent us from speculation and uncertainty. Research on the sharia label on shares has never been found, therefore this study aims to analyze whether the sharia label has an effect on determining investor investment decisions with the existence of a religion that is believed to be a moderating variable. The grand theory used in this research is Behavioral Finance Theory with Bias Framing as a derivative. This type of research is qualitative with a total sample of 66 Darwan Ali Sampit University students taken using the purposive sampling method. This research method uses experiments and analyzed using logistic regression with logit function. The results of this study indicate that the sharia label has no effect on investors' decision to invest in shares, but when the investor is a Muslim, the investor's decision to invest in sharia shares will be stronger.